A Comparative Study on the Usage of HRIS in the IT/ITES, Services, and Manufacturing Sectors in the Indian Scenario - Srivastava, Sanjay; Bagga, Teena (Prabandhan: Indian Journal of Management, 2015)
Information systems have grown as an integral part of every business process in an organization, be it a large of small organization. Human resource information system (HRIS) forms an integration between human resource management (HRM) and information technology (IT). Its usage has aided HR to shed its administrative burden to a great extent. The primary purpose of this study is to understand the HRIS usage in various functionalities of the HR department in the Indian scenario. The data was collected through a self-administered questionnaire from 269 organizations; the respondents were IT and HR managers. The study compares the usage level of HRIS among the three major sectors in India, that is, IT/ITES, services, and manufacturing sectors. In addition, this study also explores the differences between large and SME organizations under these sectors. Independent t - test and ANOVA were used for drawing these comparisons. The results show the variation in the usage of HRIS features among the different groups. In addition, a massive gap was found to be evident in the usage of HRIS, which can be tapped by the HRIS software providers for business development.